Visualizing Femicides: Comparing Argentina with Neighbouring Latin American Countries - Molfino, María Gabriela (2024)
This paper explores the application of data visualization techniques to analyze femicides, conducting a comprehensive comparative study between Argentina and its neighboring countries. Through the application of visualization approaches, we aim to uncover patterns, trends, and critical insights that contribute to a deeper understanding of the prevalence, dynamics, and impact of femicides in these regions. In this article, we introduce a data visualization dashboard focused on femicides in Argentina and Latin America. Our study examines different facets of femicide in the region, exploring the connections between femicide rates and factors such as intimate partner violence, migration rates, unemployment, and educational attainment from 2017 to 2022.